Growth chamber and field evaluation of physiological factors of two watermelon genotypes - Goitseone Malambane (Elsevier, 2021)
Drought is a major threat to food security worldwide, and drought-tolerant plants are a convenient model to study the mechanisms underlying drought tolerance. Some of the studies on drought tolerance mechanisms have been performed under controlled environments, while others have been undertaken under natural field conditions; nevertheless, it is important to evaluate the similarities and differences between the results obtained in each case. In this study, the physiological responses of a drought-tolerant wildtype and a drought-susceptible watermelon cultivar were evaluated under both natural and artificial environments. Although different in intensity, the trend of physiological responses was similar in both environments. After five days of exposure to drought, the wildtype showed a sharper decline (80.91%) in CO2 assimilation in the field than in a growth chamber (65.81%). The non-photochemical quenching (NPQ) parameters showed lower values in the cultivar than in the wildtype, regardless of growth environment; additionally, final NPQ values recorded for the wildtype were significantly higher in field plants than in those grown in a growth chamber. Regression analysis showed a highly significant correlation between NPQ and photosynthesis in the wildtype in both environments, while the relationships were non-significant in field-cultivated watermelon. These findings demonstrate that artificial conditions can be used to study the trends of plant responses to environmental stress, but results must be interpreted with caution.